ANALYSIS AND RECONSTRUCTION OF THE PRACTICUM WORKSHEET 'THE EFFECT OF TEMPERATURE ON CATALASE ENZYME ACTIVITY - Anggia Fitri Damayanti; Suhara Suhara; Bambang Supriatno; Amprasto Amprasto (Physics Education Study Program, Faculty of Education and Teacher Training, UNSIQ, 2024)
Practicum is a learning activity that can develop students' cognitive, affective, and psychomotor abilities. Practicum activities are very important, especially in biology learning. One of the concepts in biology that can be explored through practicum is the activity of the enzyme catalase. This study aims to analyze the practicum worksheet on catalase enzyme activity, specifically focusing on the effect of temperature on catalase activity. The analysis is conducted using Novak & Gowin's vee diagram, which includes focus question, object/event, theory/concept, record/transformation, and knowledge claim. The reconstruction of the practicum procedure is carried out to ensure that the activities align with the fundamental concepts being studied. This allows students to link the practicum procedures with the underlying concepts, enabling them to analyze and build their understanding of the effect of temperature on catalase enzyme activity.